GLOBALISASI KONTEMPORER DAN FEMINISME TRANSNASIONAL DIGITAL: ANALISIS JARINGAN TEKSTUAL @jakartafeminist - Rifka Annisa Hermanto (Jurnal Sosioteknologi, 2022)
The internet and social media have influenced how feminist activists work today. In Indonesia, digital feminist activism was found to have been initiated by young women to deconstruct the general view related to women's empowerment, gender equality, networking, and mobilizing the protest constituents to the street. The opening of networks between countries by the internet has the potential to be the "bridge" for global feminism’s vision to the local agenda of feminist activists. Hence, this study aims to provide a discourse on the textual network of digital activism in the case of Jakarta Feminist. As a result, although the Jakarta Feminists have adopted a form of movement and entered the global network, the existing discourse shows the dominance of local issues and agendas such as gender-based violence, women’s representation, and human rights. Thus, they adapt the feminism concept to the local context. Keywords: Digital Feminist Activism, Textual Network Analysis, Jakarta Feminist